Exploring cultural technological mathematics learning in vocational schools for creative thinking - Wilda Febriana Wijayanti; Ida Dwijayanti; Lukman Harun (CV. FOUNDAE, 2026)
Background: Mathematics education in vocational schools faces challenges in fostering students’ creative thinking, particularly in understanding abstract concepts and generating alternative solutions. Classroom practices often emphasize procedural replication, while teachers encounter difficulties in addressing diverse learning needs, highlighting the need for innovative, contextual, and culturally responsive approaches. Aims: This study aims to strengthen vocational students’ creative thinking in mathematics by designing an integrated instructional model that combines pedagogy, technology, and cultural elements. Methods: A qualitative design thinking approach was applied through the stages of Empathize, Define, Ideate, Prototype, and Test/Evaluate. Data were collected using questionnaires, interviews, and classroom observations to identify student and teacher needs. The proposed model was further examined through a meta-analysis using effect size calculations to synthesize findings from relevant empirical studies. Results: The findings indicate that students need more flexible, innovative, and culturally meaningful learning experiences. An instructional prototype, Gema-Batik, was developed by integrating Project-Based Learning, ethnomathematics, GeoGebra, and jBatik within a design thinking framework. The model emphasizes problem orientation, exploration, digital modeling, motif creation, and presentation, targeting creative thinking indicators such as fluency, flexibility, originality, and elaboration. Meta-analytic results show a high pooled effect size, indicating strong potential to enhance creative thinking and related competencies. Conclusion: The Gema-Batik model offers a novel, culturally grounded, and technology-integrated approach that contributes both theoretically and practically to vocational mathematics education, particularly in fostering creative thinking aligned with the demands of creative industries.